2011
DOI: 10.2174/1874357901105010109
|View full text |Cite
|
Sign up to set email alerts
|

GM-CSF Fails to Improve Immune Responses to Booster Hepatitis B Vaccination in HIV-Infected Individuals

Abstract: Background:Hepatitis B (HBV) vaccination is an important preventive intervention for HIV-infected population. Data regarding booster HBV vaccine for persons with low HBV surface antibody (sAb) titers after vaccination in this immunocompromised population is lacking.Methods:We randomized 60 HIV-infected subjects lacking HBV protection after completion of 3 doses of HBV vaccine to receive a booster dose of HBV vaccine with 250mcg GM-CSF as an adjuvant or booster vaccine alone.Results:GM-CSF was safe with expecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…But on day 210, the seroconversion rate did not differ (72 vs 60%, p D 0.23). Two RCT by Overton et al, 73,100 however, did not confirm these results. In the first one, their patients received 250mg GM-CSF as an adjuvant to a 40 mg accelerated schedule at 0-1-3 months but the vaccine-alone group had better response rates (65.2 vs 52.4%, NSD).…”
Section: Is There a Place For Adjuvants For Hbv Vaccination In Peoplementioning
confidence: 90%
See 2 more Smart Citations
“…But on day 210, the seroconversion rate did not differ (72 vs 60%, p D 0.23). Two RCT by Overton et al, 73,100 however, did not confirm these results. In the first one, their patients received 250mg GM-CSF as an adjuvant to a 40 mg accelerated schedule at 0-1-3 months but the vaccine-alone group had better response rates (65.2 vs 52.4%, NSD).…”
Section: Is There a Place For Adjuvants For Hbv Vaccination In Peoplementioning
confidence: 90%
“…Numerous studies, from retrospective studies to randomized control trials (RCT), have found a correlation between undetectable HIV RNA, a high CD4 cell count and higher vaccination success. 19,20,23,27,30,60,63,75,[93][94][95][96][97]100 The HIV viral load even seems to be more important than the CD4 count [19, 21, 23,], even though a positive correlation between the CD4 cell count at the time of (re)vaccination and the response to vaccination was observed in many studies. 10,11,20,22,23,95 Other predictors of a poor response include HCV co-infection, poor general health status and occult hepatitis B 7 often observed in people living with HIV.…”
Section: Reinforced Vaccination Strategies In People Living With Hiv mentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that when the HBV-S gene is fused to the GM-CSF gene, the immune responses induced by HBV-DNA plasmids both in normal and HBV-transgenic mice can be strengthened, and HBV-DNA plasmids fused with GM-CSF may be used for prevention and treatment [142], but meanwhile, it also showed that GM-CSF was not able to improve the antibody (Ab) titer or the development of protective immunity by the HBV vaccination in healthy adult nonresponders [142]. Recently, another study revealed that GM-CSF failed to improve responses to the booster HBV vaccination in HIV-infected individuals [143]. Thus, whether GM-CSF is an optimal vaccination strategy needs to be evaluated.…”
Section: Experimentally Therapeutic Applications Of Cytokines and Thementioning
confidence: 99%
“…We excluded 43 studies some of which were non-randomised (Abzug 2009; Alaei 2003; Bailey 2008; Carne 1987; Horster 2010; Kalinowska-Nowak 2007; Koblin 1999; Lao-Araya 2011; Loke 1990; Paitoonpong 2008; Sellar 2009; Thaithumyanon 2002; Wilson 2001; Wursthorn 2011), not in PLHIV (Altuntas 2011; Mehta 2010; Mehta 2010a; Miller 1989; Odaka 1988; Pasricha 2005; Thompson 1998) testing adjuvants to hepatitis B vaccine (Cooper 2005a; Cooper 2008; Overton 2010; Overton 2011; Sasaki 2003; Sayad 2012); testing modalities of administering hepatitis B vaccine (Bunupuradah 2011; de Vries-Sluijs 2011; Flynn 2011; Fonseca 2005; Hwang 2010; Launay 2011; McQuillan 2010) vaccines targeting other conditions (Johnson 1999; Kintu 2013; Launay 2011a). See Characteristics of excluded studies.…”
Section: Resultsmentioning
confidence: 99%